PEMBINAAN EKSTRAKURIKULER DALAM MEMPERSIAPKAN SISWA SDI NASIPANAF PADA KEGIATAN O2SN TAHUN 2020 - Lukas M. Boleng; Yudabirull Arif; Gerson Nifu (Nusa Cendana University, 2020)
ABSTRACTThe problem formulation in this research is how the extracurricular coaching in preparing Extracurricular Guidance in Preparing Nasipanaf Elementary School Students in O2SN activities in 2020. The problem formulation in this Research is how the extracurricular coaching in preparing Extracurricular Guidance in Preparing Nasipanaf SDI Students in O2SN activities in 2020. 02SN SDI Nasipanaf students in 2020. The purpose of this study was to find out extracurricular coaching in preparing students of 02SN SDI Nasipanaf in 2020. the type of research used in this study was qualitative naturalistic while the isolation used in this study was grade V of SDI Nasipanaf students totaling 23 the sample of people used in the study were 15 students. Data collection was carried out by interviewing observation techniques and documentation of extracurricular analysis activities carried out 3 times in a week. This guidance showed the results of students representing schools as city-level championships, this was also done by providing students and school coaching in extracurricular activities. From the results of observations and interviews of principals and Physical Education teachers where researchers with findings from the preparation and coaching stages undertaken by Physical Education teachers strongly support students in performing in sports and the school principal also fully supports extra-curricular activities carried out in schools andexpectations from the school principal so that children can win the O2SN activity at the city level.Keywords: Extracurricular activities at the O2SN SDI Nasipanaf town in Kupang